N-acetyl Cysteine Overdose Induced Acute Toxicity and Hepatic Microvesicular Steatosis by Disrupting GSH and Interfering Lipid Metabolisms in Normal Mice - Ming-Shiun Tsai; Gunn-Guang Liou; Jiunn-Wang Liao; Pin-Yen Lai; Di-Jie Yang; Szu-Hua Wu; Sue-Hong Wang (MDPI AG, 2024)
N-acetyl cysteine (NAC) is a versatile drug used in various conditions, but the limitations and toxicities are not clear. The acute toxicity and toxicological mechanisms of an intraperitoneal injection of NAC in normal mice were deciphered. The LD50 for male and female BALB/cByJNarl mice were 800 mg/kg and 933 mg/kg. The toxicological mechanisms of 800 mg/kg NAC (N800) were investigated. The serum biomarkers of hepatic and renal indices dramatically increased, followed by hepatic microvesicular steatosis, renal tubular injury and necrosis, and splenic red pulp atrophy and loss. Thus, N800 resulted in mouse mortality mainly due to acute liver, kidney, and spleen damages. The safe dose (275 mg/kg) of NAC (N275) increased hepatic antioxidant capacity by increasing glutathione levels and catalase activity. N275 elevated the hepatic gene expressions of lipid transporter, lipid synthesis, β-oxidation, and ketogenesis, suggesting a balance between lipid production and consumption, and finally, increased ATP production. In contrast, N800 increased hepatic oxidative stress by decreasing glutathione levels through suppressing Gclc, and reducing catalase activity. N800 decreased the hepatic gene expressions of lipid transporter, lipid synthesis, and interferred β-oxidation, leading to lipid accumulation and increasing Cyp2E1 expression, and finally, decreased ATP production. Therefore, NAC doses are limited for normal individuals, especially via intraperitoneal injection or similar means.